Perlindungan Hukum Terhadap Anak Dalam Proses Penyidikan di Kepolisian Resor Kota Jayapura - Asmarani, Nur (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This study aims to find out, understand and explain the implementation of legal protection for children in the investigation process at the Jayapura City Police and the obstacles in the implementation of legal protection for children in Jayapura City. The research method used in this study is normative juridical, namely reviewing the applicable laws and regulations and the discussion in this study is normative. The discussion in question is intended to review rational structures, applicable legal systems, this is done for scientific processing of normative legal materials, so that the formation of law will be more professional. The results of this study reveal that the implementation of legal protection for children in the investigation process at the Jayapura City Police is still limited, because in terms of its regulations in this case the SPPA law has responded to the Convention on the Rights of the Child compared to previous laws. While the obstacles in the implementation of legal protection for children in Jayapura City are distinguished from internal and external aspects. Internal obstacles are mainly in terms of limited human resources, lack of experts, especially psychologists and psychiatrists, lack of finance, facilities and infrastructure. While external obstacles such as culture, religion and social.